Use of phosphodiesterase 4 inhibitor in patients with psoriatic arthritis - V. I. Mazurov; E. A. Trofimov (Современная ревматология)
Psoriatic arthritis (PsA) is a chronic inflammatory disease of the joints, spine, and entheses, which is associated with psoriasis. The pathological process is localized mainly in the tissues of the locomotor system and leads to the development of erosive arthritis, intra-articular osteolysis, and spondyloarthritis. Nonsteroidal anti-inflammatory drugs, glucocorticoids, disease-modifying antirheumatic drugs (DMARDs), biological agents (BAs), and targeted synthetic drugs (or signaling pathway blockers) are used to treat PsA. The latter group of drugs includes apremilast, a phosphodiesterase 4 inhibitor. Recent data of controlled studies suggest that apremilast is effective and safe in treating psoriasis and PsA. Prospects for the use of apremilast in PsA are associated with the possibility of giving the drug to patients because of the inefficacy of DMARDs or BAs.